Elevated Blood C-Reactive Protein Levels in Patients With Epilepsy: A Systematic Review and Meta-Analysis - Zhong, Rui; Chen, Qingling; Li, Mengmeng; Zhang, Xinyue; Lin, Weihong (Frontiers in Neurology, 2019)
Background: In recent years, increasing attention has been paid to the association between C-reactive protein (CRP) levels and epilepsy. However, studies concerning CRP levels in epilepsy have also yielded conflicting results. Thus, the objective of the present study is to systematically review the evidence and conduct a meta-analysis to investigate CRP levels in epileptic patients compared with healthy controls. Methods: A systematic search of PubMed, EMBASE, and the Cochrane Library was performed for eligible studies. Standardized mean differences (SMDs) with 95% confidence intervals (95% CIs) were used as a measure to assess the association between CRP and epilepsy. Results: In total, 16 case–control studies were included in the present meta-analysis, which comprised 1918 individuals. Combined results indicated that epileptic patients had significantly increased CRP levels in peripheral blood compared with healthy controls (SMD = 0.43; 95% CI: 0.19–0.67). In addition, subgroup analyses by age demonstrated that significant differences in blood CRP levels between epileptic patients and healthy controls could be found in adults (SMD = 0.47; 95% CI: 0.21–0.73) but not children (SMD = 0.26; 95% CI: −0.48–0.99). Conclusion: The present meta-analysis shows that the CRP levels in peripheral blood were significantly increased in epileptic patients compared to healthy controls, indicating a significant association between inflammation and epilepsy. Epileptic seizures may be associated with the inflammatory response.